Information technology governance model for a low resource institution with fragmented IT portfolio - Ngqondi, T.; Mauwa, H. (South African Journal of Higher Education, 2020)
The emergence of information technology governance in higher education has emerged as important for aligning information technology goals with that of institutions in order to achieve the mission and vision of institutions. Even though higher education institutions in South Africa have some form of information technology governance or information technology strategic committee in place, they are still struggling to operationalize their mandate effectively in order to achieve their objectives. The struggle is even more in settings that are low on resources and where the information technology portfolio is highly fragmented. In this article, an information technology governance model suitable for low resource settings and fragmented information technology portfolios is proposed to assist institutions having this type of setting achieve successful strategic information technology alignment. Case study research was used to: 1) understand information technology challenges that an institution with this type of setting faces and; 2) understand how other similar institutions have implemented their information technolgy governance. The findings from the case studies contributed to the development of an effective information technology governance model suited to these institutions with low resource settings and having fragmented information technology portifolios. Initial evaluation of the model using existing literature review, existing information technology governance frameworks and case studies used in the study indicate the validity of the model.